Swallowing in Patients with Mental Disability - Analysis of 189 Swallowing Video Endoscopies - Pirana, Sulene; Oliveira, Marcela; Pissini, Fabiana; Andrade, Raíssa (International Archives of Otorhinolaryngology, 2019)
Introduction Feeding, swallowing and breathing are fundamental activities for the survival and well-being of humans; these functions are performed by the most complex neuromuscular unit of the human body, which, when altered, may raise morbidity and mortality rates.Objective To evaluate deglutition in patients with mental disability in order to determine the incidence and the severity of dysphagia.Methods A total of 189 institutionalized adult patients with mental disability were analyzed using a 3.2 mm flexible fiberscope (Machida, Japan 1995). The following food consistencies were tested: pasty, thickened liquid and liquid.Results Among the total of 189 patients, 101 (53.4%) were female aged between 14 and 55 years old. Most of them 120 (63.5%) had profound mental deficiency, 58 (30.7%) had severe mental deficiency, 9 (4.8%) had moderate mental deficiency, and 2 (1.1%) had mild mental deficiency. Gender and the degree of mental deficiency did not influence significantly the degree of dysphagia. Age, degree of disability and interaction between age groups and degrees of disability influenced significantly the degree of dysphagia. Younger patients are more likely to present more severe dysphagia. Stabilization occurs between 31 and 40 years of age, and above this age, a greater chance of less severe dysphagia, because the increase in the degree of mental deficiency decreases the probability of more severe dysphagia.Conclusion The population that mostly presented severe dysphagia was characterized by being mostly female, with profound mental deficiency, with an average age of 36.7 years. There was no relationship between gender and the degree of mental disability concerning the degree of dysphagia.
Keywords: deglutition disorders; mentally disabled persons; video endoscopy